2014
DOI: 10.2174/13816128113199990427
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids and Schizophrenia: Therapeutic Prospects

Abstract: Approximately one third of patients diagnosed with schizophrenia do not achieve adequate symptom control with standard antipsychotic drugs (APs). Some of these may prove responsive to clozapine, but non-response to APs remains an important clinical problem and cause of increased health care costs. In a significant proportion of patients, schizophrenia is associated with natural and iatrogenic metabolic abnormalities (obesity, dyslipidaemia, impaired glucose tolerance or type 2 diabetes mellitus), hyperadrenali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Oral CBD before ⌬ 9 -THC (600 mg, administered 3.5 h before 1.5 mg ⌬ 9 -THC iv) inhibited both paranoia and impairment of episodic memory (243). It was hypothesized that CBD in combination with a CB1 receptor antagonist could target the metabolic, inflammatory, and stressrelated components of the schizophrenia phenotype (731). Indeed, CBD may attenuate immune responses associated with psychotic disorders (182), as it inhibits both the production of proinflammatory cytokines and microglia activation (534).…”
Section: Psychosismentioning
confidence: 99%
“…Oral CBD before ⌬ 9 -THC (600 mg, administered 3.5 h before 1.5 mg ⌬ 9 -THC iv) inhibited both paranoia and impairment of episodic memory (243). It was hypothesized that CBD in combination with a CB1 receptor antagonist could target the metabolic, inflammatory, and stressrelated components of the schizophrenia phenotype (731). Indeed, CBD may attenuate immune responses associated with psychotic disorders (182), as it inhibits both the production of proinflammatory cytokines and microglia activation (534).…”
Section: Psychosismentioning
confidence: 99%
“…The 2 major phyto-cannabinoid constituents with central nervous system activity are THC, responsible for the euphoric and mind-altering effects, and CBD, which lacks these psychoactive effects. Preclinical and clinical studies show CBD possesses a wide range of therapeutic properties, including antipsychotic, analgesic, neuroprotective, anticonvulsant, antiemetic, antioxidant, anti-inflammatory, antiarthritic, and antineoplastic properties (see [11,12,[16][17][18][19] for reviews). A review of potential side effects in humans found that CBD was well tolerated across a wide dose range, up to 1500 mg/day (orally), with no reported psychomotor slowing, negative mood effects, or vital sign abnormalities noted [20].…”
Section: Cbd Pharmacology Relevant To Anxiety General Pharmacology Anmentioning
confidence: 99%
“…CBD has a broad pharmacological profile, including interactions with several receptors known to regulate fear and anxiety-related behaviors, specifically the cannabinoid type 1 receptor (CB 1 R), the serotonin 5-HT 1A receptor, and the transient receptor potential (TRP) vanilloid type 1 (TRPV1) receptor [11,12,19,21]. In addition, CBD may also regulate, directly or indirectly, the peroxisome proliferator-activated receptor-γ, the orphan G-protein-coupled receptor 55, the equilibrative nucleoside transporter, the adenosine transporter, additional TRP channels, and glycine receptors [11,12,19,21].…”
Section: Cbd Pharmacology Relevant To Anxiety General Pharmacology Anmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting that many studies suggest that major psychiatric conditions are associated with inflammation [171]; in particular, there appears to be a correlation between suicide and inflammatory markers [172]. It is therefore of particular relevance that many anti-depressants apparently inhibit the ETC [173], suggesting that some of their effects could be explained by hormesis.…”
Section: Is Thinking Anti-inflammatory?mentioning
confidence: 99%